Diagnostic Accuracy of the GenoType MTBDRsl Assay for Rapid Diagnosis of Extensively Drug-Resistant Tuberculosis in HIV-Coinfected Patients - Kontsevaya, Irina (American Society for Microbiology, 2013)
The Russian Federation is a high-tuberculosis (TB)-burden country with high rates of Mycobacterium tuberculosis multidrug resistance (MDR) and extensive drug resistance (XDR), especially in HIV-coinfected patients. Rapid and reliable diagnosis for detection of resistance to second-line drugs is vital for adequate patient management. We evaluated the performance of the GenoType MTBDRsl (Hain Lifescience GmbH, Nehren, Germany) assay on smear-positive sputum specimens obtained from 90 HIV-infected MDR TB patients from Russia. Test interpretability was over 98%. Specificity was over 86% for all drugs, while sensitivity varied, being the highest (71.4%) for capreomycin and lowest (9.4%) for kanamycin, probably due to the presence of mutations in the eis gene. The sensitivity of detection of XDR TB was 13.6%, increasing to 42.9% if kanamycin (not commonly used in Western Europe) was excluded. The assay is a highly specific screening tool for XDR detection in direct specimens from HIV-coinfected TB patients but cannot be used to rule out XDR TB.